Public Pickup / Ahmad Dzulkifli, Muhammad Aizuddin Mohd Alias … [et al.] - Dzulkifli, Ahmad; Mohd Alias, Muhammad Aizuddin; Mohammed Samsudin, Sharul Aiman (2017)
Public transportation systems include a variety of transit options such as buses, light rail, grab and bicycle. These systems are available to the general public, may require a fare, and run at scheduled times. Develop country have use public transport application to make people ease to plan their journey.